Application of the Theory of Planned Behavior to Identify Variables Related to Academic Help Seeking in Higher Education - Bornschlegl, Madeleine; Townshend, Kishani; Caltabiano, Nerina Jane (Frontiers in Education, 2021)
Universities admit and enrol increasingly diverse student cohorts with varying academic entry standards. To increase student success, universities offer academic support to students, however, often students do not engage in or access this academic support. Building on the Theory of Planned Behavior and a comprehensive literature review, this study aims to identify personality variables, background variables and variables related to the Theory of Planned Behavior that can predict academic help seeking in higher education to inform the design of engaging and accessible academic support. Quantitative data were collected via an online survey across a range of different disciplines and undergraduate year levels at an Australian university. Structural Equation Modelling revealed that public stigma, self-stigma, extraversion, agreeableness, neuroticism, gender and the Theory of Planned Behavior variables perceived behavioural control, subjective norm and attitude towards help seeking play a role in predicting intentions to seek academic help, and academic help-seeking behaviour. Findings indicate that 20% of the variance of help-seeking intentions but only 5.7% of the variance of academic help seeking could be explained. Findings are discussed as to how they can inform interventions to increase help-seeking intentions and behaviour. Finally, this study explores how to overcome the present intention-behaviour gap.